Dynamic Amodal Completion Through the Magic Wand Illusion. (December 2019) - Tyler, Christopher W.
In the Magic Wand effect, an overlying figure of the same color as its background is revealed by the motion of a wand behind it. The occluding figure is inferred by integration of the occluding edge information over time. The overlying figure is perceived by modal completion, while the wand and the background underneath are perceived by amodal completion. This illusion is compared with its predecessor from nearly two centuries ago, the Plateau Anorthoscopic Illusion, in which an object is recognizable when moved behind a slit.